Sensitivity Analysis of FDS Program Parameters for Determining the Stand-Off Distances in Fire Safety Solutions for Buildings—Slovak Case Study - Dorota Hodúlová; Patrik Mitrenga; Stanislava Gašpercová; Iveta Marková (Fire)
Fire safety solutions for buildings in Slovakia are addressed by legislation and Slovak technical standards, which are not legally binding, but their wording is mandatory if they are referred to in an implementing regulation. Fire safety solutions for buildings in Slovakia are therefore limited mainly by legislation and technical standards. The use of fire models in fire safety solutions for buildings is common across the world, but these tools are not used in Slovakia. Their use is not prohibited by law, but it is always necessary to prove the applicability and correctness of the outputs. The paper deals with a case study of Slovak implementation of fire models when discussing the stand-off distances from fully fire-open areas. The Slovak case study addresses the fire safety solutions for buildings under the conditions of the Slovak Republic. To utilize the fire models in practice, the threshold conditions for the use of the selected FDS fire model needed to be established. This process is called a sensitivity analysis, and it is conducted based on the utilized simulation method. Based on the sensitivity analysis of FDS, the exact values of parameters can be determined, the use of which in the implementation of fire models in practice will allow accurate outputs and values of stand-off distances from fully fire-open areas in the conditions of the Slovak Republic to be obtained.